Changes in water column and sedimentary environments at the onset of the Messinian salinity crisis: Insights from an onshore deep-water section (Govone, NW Italy) - Mathia Sabino; Francesco Dela Pierre; Marcello Natalicchio; Daniel Birgel; Susanne Gier; Jörn Peckmann (PANGAEA, 2021)
The data set was used to trace the impact of the advent of the late Miocene Messinian salinity crisis (MSC) 5.97 Ma ago in the northern Mediterranean (Piedmont Basin, NW Italy) on the water column and sedimentary environments. We analysed shale/marl couplets deposited from about 6.07 to 5.92 Ma in distal areas of the Piedmont Basin (Govone section; 44°48'08''N; 8°07'34''E). The analyses included X-ray diffraction (XRD), bulk-rock carbon (δ13C) and oxygen (δ18O) stable isotopes, total organic (TOC) and inorganic (TIC) carbon, and lipid biomarkers. XRD analyses aimed to investigate carbonate mineralogy, revealing the occurrence of calcite and dolomite. Dolomite represents the only carbonate phase after the MSC onset, with an overall increase indicated by TIC investigations. Stable isotope ratios suggested the involvement of microbial activity in the precipitation of dolomite (δ13C) and helped the reconstruction of the physical characteristic of the fluids from which the carbonate phase precipitated (δ18O). Lipid biomarker analyses focused on the acyclic terpenoid lycopane, the cyclic terpenoid tetrahymanol, the isoprenoid diphytanyl glycerol diether C20-20 archaeol, isoprenoid glycerol dibiphytanyl glycerol tetraethers (GDGTs), and the carotenoid isorenieratane. The lipids provided new information on the archaeal community thriving in the distal areas of the Piedmont Basin and allowed the reconstruction of physical and chemical properties of the water column (stratification, photic zone euxinia, redox conditions). Ultimately, the data set revealed how physicochemical properties of the water column controlled the stratigraphic architecture of the sediments deposited during the first stage of the MSC.